Storytelling as a Teaching Tool: Some Reflections from Experiences with Undergraduate Students - D’Avanzo, Stefania (ALLiED, 2025)
In recent years, storytelling has been increasingly used to support teaching and learning in higher education. Indeed, storytelling has been considered as an integral component of learning as it has been shown to be able to support students in their sense-making processes (Mokhtar et al. 2011; Alkaaf 2017; Abrahamson 1998). This study is aimed at exploring corporate storytelling-based tasks and activities involving undergraduate students, while uncovering linguistic and multimodal methods and tools involved in teaching English as a foreign language in a Business Department. While integrating the perspectives of scholars from different fields (Cheng et al. 2021; Smeda et al. 2014) the present contribution highlights the need to adapt the storytelling methods to specific goals and learning needs. Therefore, different ways to work with stories are discussed, along with structured approaches to adopt when students are new to storytelling.